Patients' perceptions of barriers to self-managing bipolar disorder: A qualitative study. (November 2016) - Blixen, Carol; Perzynski, Adam T; Bukach, Ashley; Howland, Molly; Sajatovic, Martha
Background: Self-management of bipolar disorder (BD) is challenging for many individuals. Material: Interviews were used to assess perceived barriers to disease self-management among 21 high-risk patients with BD. Content analysis, with an emphasis on dominant themes, was used to analyze the data. Results: Three major domains of barriers emerged: individual barriers (psychological, knowledge, behavioral and physical health); family/community-level barriers (lack of support and resources); and provider/healthcare system (inadequate communication and access to care). Conclusion: Care approaches providing social and peer support, optimizing communication with providers and integrating medical and psychiatric care may improve self-management of BD in this vulnerable population.